Contemporary issues in South African education - Mncube, Vusi; Wolhuter, Charl; Adelabu, Oluwatoyin J; Gubevu, Bongumusa; Nyawo, Nokuphumula; Tyilo, Nonzukiso; Matshoba, Thobeka; Olawale, Babawande E; Hendricks, Winston (AOSIS, 2025)
South African education is widely regarded as being in crisis, facing deep and persistent challenges. This reality is starkly reflected in international assessments such as the 2021 Progress in International Reading Literacy Study (PIRLS), where South Africa ranked last among 43 countries and recorded the steepest decline of all participants. This book brings together leading scholars to examine critical issues shaping South African education today. Each chapter focuses on a key topic, offering authoritative insights into the system’s weaknesses and potential pathways for improvement. Employing qualitative research methods, the authors provide in-depth analyses that enrich scholars’ understanding of the country’s educational landscape and point toward solutions for a more equitable and effective system.